KENDALA PROSES MEDIASI DI PENGADILAN DALAM PENYELESAIAN SENGKETA ALTERNATIF TERHADAP ALAS HAK ATAS TANAH (MENURUT PERMA NOMOR 1 TAHUN 2016) - Remy Ahmad Rashad Widyanto, (2021)
Land is one of the natural resources that is very important for human survival, the relationship between humans and land is not just a place to live, but more than just that relationship but as a resource for human survival itself. Especially in today's modern world where developments and developments occur very quickly, land disputes always exist and become an unavoidable fact or concrete evidence of today's society. Not everyone wants to be involved in a dispute, but sometimes the dispute does arise and has become a factor that must be anticipated and faced. The obstacles in taking the mediation procedure at the District Court and the Supreme Court, basically mediation in the Court is an obligation to be followed by the litigating parties, such as the reluctance of one of the parties to attend mediation is motivated by not being serious about making peace so that if you do not follow the mediation process, then the decision will be null and void. In addition, the absence of a mediator certificate makes the judge unable to mediate a case, and the obstacle during mediation is the absence of advocate support for the parties to participate in mediation. The absence of advocate support is motivated by the interests of advocates to obtain material only. In the concept of justice referring to John Rawls' theory of justice, the justice to be achieved in mediation is procedural justice because one aspect of procedural justice is related to the discussion of how to provide justice in the legal process, including the process of resolving civil disputes through Mediation. It was concluded that explicitly, Supreme Court Rules Number 1 of 2016 concerning Mediation Procedures in Courts is an implementation of the Civil Procedure Code.